2014
DOI: 10.1155/2014/757325
|View full text |Cite
|
Sign up to set email alerts
|

Considering District and School Factors and Their Relationship to ACT Performance in North Carolina: An Examination of the ACT Pilot Results

Abstract: Since 2001 several states have adopted the requirement that high school students either take the SAT or ACT to assess high school programs or assist students in accessing post-secondary-educational opportunities. In 2012 the state of North Carolina adopted a new accountability program that included the ACT as a measure of college readiness. Previous research on the relationship between school districts and school level performance found that district size had a role in school achievement. This study looked at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…These findings were consistent with other studies on gender, 15,[20][21][22][23][24] age, 15,[20][21][22][25][26][27] and parental educational level. [28][29][30] Therefore, our study further supports CT disposition as a trait that does not depend on general personal characteristics.…”
Section: -10supporting
confidence: 77%
“…These findings were consistent with other studies on gender, 15,[20][21][22][23][24] age, 15,[20][21][22][25][26][27] and parental educational level. [28][29][30] Therefore, our study further supports CT disposition as a trait that does not depend on general personal characteristics.…”
Section: -10supporting
confidence: 77%
“…In other words, district leaders are expected to have an active role in making decisions on direction setting, curriculum, PD for teachers and school leaders, personnel policies, resourcing, and developing supportive structures to promote teaching, learning, and leadership in schools. Other studies have also reported the importance of these decision areas (e.g., Honig, M., 2012; Kaniuka, 2014; Kerr, Marsh, Ikemoto, Darilek, & Barney, 2006; Leithwood et al, 2004; Marsh et al, 2005; Perry & McDermott, 2003; Rorrer, Skrla, & Scheurich, 2008). Thus, based on the literature, in this study, we focused our inquiry on the influence of districts and school principals on seven school decisions: standards, curriculum, content of teachers’ PD programs, evaluating teachers, hiring teachers, discipline, and spending budgets.…”
Section: Empirical Studies On Power Relationships and Decision Domainsmentioning
confidence: 96%